Collagen V Is a Potential Substrate for Clostridial Collagenase G in Pancreatic Islet Isolation - Hiroki Shima; Akiko Inagaki; Takehiro Imura; Youhei Yamagata; Kimiko Watanabe; Kazuhiko Igarashi; Masafumi Goto; Kazutaka Murayama (Journal of Diabetes Research)
The clostridial collagenases, H and G, play key roles in pancreatic islet isolation. Collagenases digest the peptide bond between Yaa and the subsequent Gly in Gly-Xaa-Yaa repeats. To fully understand the pancreatic islet isolation process, identification of the collagenase substrates in the tissue is very important. Although collagen types I and III were reported as possible substrates for collagenase H, the substrate for collagenase G remains unknown. In this study, collagen type V was focused upon as the target for collagenases. In vitro digestion experiments for collagen type V were performed and analyzed by SDS-PAGE and mass spectrometry. Porcine pancreatic tissues were digested in vitro under three conditions and observed during digestion. The results revealed that collagen type V was only digested by collagenase G and that the digestion was initiated from the N-terminal part. Tissue degradation during porcine islet isolation was only observed in the presence of both collagenases H and G. These findings suggest that collagen type V is one of the substrates for collagenase G. The enzymatic activity of collagenase G appears to be more important for pancreatic islet isolation in large mammals such as pigs and humans.